Penerimaan Diri Ibu Tentang Perubahan Yang Terjadi Pada Masa Menopause - Dodik Arso Wibowo; Widyasih Sunaringtyas (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Women who experience menopause undergo hormonal changes that lead to both physical and psychological changes. Therefore, self-acceptance is necessary in facing these transitions. Self acceptance in mothersis useful for increasing self confidence in mothers which is usefull for increasing self confidence and self acceptance in mother during menopause, especialy changes during menopause. This study aims to determine the self-acceptance of mothers regarding the changes experienced during menopause in Pelem Hamlet, Pelem Village, Pare Sub-district, Kediri Regency. This research employed a descriptive design, with a population of 49 respondents and a sample of 30 respondents, selected using purposive sampling. The study was conducted from March 20 to April 30, 2025, in Pelem Hamlet, with the research variable being mothers' self-acceptance of changes during menopause. Data were collected using a questionnaire and analyzed quantitatively using percentages. The results showed that out of 30 respondents, the majority (27 respondents or 90%) had good self-acceptance, while a small portion (3 respondents or 10%) had moderate self-acceptance.Factors such as maternal age, age at last menstruation, education level, occupation, prior information about menopause, sources of information, living arrangements, and husband’s monthly income influenced the level of self-acceptance.the most dominan faktorin this case is education ,which will influence the mothes, self acceptance In conclusion, the self-acceptance of mothers in Pelem Hamlet regarding menopausal changes was categorized as good. It is expected that respondents will maintain their level of self-acceptance and continue to enhance their knowledge about menopause through social media, family, or health professionals. Furthermore, mothers are encouraged to share this knowledge with others to help improve collective understanding and acceptance during the menopausal phase.